Use of the Perio-Flow Method in the Complex Treatment of Generalised Periodontitis with Moderate to Severe Disease Severity - Abdullaeva Nilufar Ikrombekovna (Scientific Trends, 2024)
Inflammatory periodontal diseases (IPD) pose significant challenges in the field of dentistry and are considered one of the complex problems to address. According to the World Health Organization, the prevalence of inflammatory periodontal diseases among the 35-44 age group, which represents the able-bodied population, exceeds 95% in Uzbekistan. Extensive scientific research is currently underway to explore new methods and enhance existing approaches to effectively manage and eliminate inflammatory conditions in the periodontium [In the past 10-15 years, numerous scientific publications in journals and dissertations have focused on improving the treatment of periodontal diseases. Despite the attention given by researchers and practicing dentists to periodontology, there have been no significant changes in the practical implementation of dental treatment and preventive measures .The high prevalence of periodontal diseases, inadequate treatment outcomes (including surgical interventions), the progressive destruction of bone tissue leading to tooth loss, and the pressing need for effective treatment and prevention strategies for this pathology underscore the urgency of the problem.
Keywords: biofilm, periodontitis, Perio-Flow.